Organizational Citizenship Behavior (OCB): Efek Budaya Organisasi dan Work-Family Conflict - Shofiyuddin Najih; Anwar Mansyur (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to determine and analyze the influence of organizational culture and Work-Family Conflict on the Organizational Citizenship Behavior of teachers under the auspices of the Islamic Education Welfare Foundation, Susukan, Cirebon Regency which consists of kindergarten, elementary, junior high, MTs, MA, SMA and SMK. This study uses a survey method using path analysis techniques including: model analysis, hypothesis testing and determining the level of influence. The process of collecting data for teachers of the Islamic Education Welfare Foundation, Susukan, Cirebon Regency used a questionnaire as a research instrument which was distributed to the entire population with the following criteria: 1) Married teachers, 2) Teachers who already had children. With these criteria, 107 samples were collected. Based on the data analysis that has been done, it can be concluded that first, Organizational Culture has a positive and significant effect on Organizational Citizenship Behavior, secondly, Work-Family Conflict has a positive but not significant effect on Organizational Citizenship Behavior.